Pengaruh Pemilihan Anti-Psikotik Pada Pasien Depresi Tanpa dan Dengan Gejala Psikotik Terhadap Lama Hari Rawat Inap - Palupi Poppy Diah; Buanasari Buanasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Antipsychotic therapy is given frequently to the patient with depressive symptoms. Antipsychotics are used to enhance the effects of antidepressants in the depressive patients. The aim of this study was to evaluate the length of stay of antipsychotic therapy selection in the depressive patient without/with psychosis symptoms. This study was conducted by quantitative method, multicenter, non-experimental approach, and cohort design study. Data were collected from medical records of 187 patients diagnosed with depression without/with psychosis symptoms from the various mental-illness hospital in Central Java Province. There was a significant difference (p 0.05) in the length of stay with the selection of antidepressants in depressive patients without psychotic symptoms, and there was no significant difference (p 0.05) in the length of stay with the selection of antipsychotic agents in depressive patients without/with psychotic symptoms.Keywords— Length of stay, depression, without/with psychosis symptoms, antipsychotic